Pengaruh Literasi Keuangan terhadap Minat Investasi Generasi Muda di Pasar Modal Indonesia - Ririn Wulandari; Robiah Aladawiyah; Muhamad Syahwildan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
Interest in investing in Indonesia's capital market has increased, especially among the younger generation. However, this phenomenon has not been fully accompanied by adequate financial literacy. This study aims to analyze the effect of financial literacy on young people's investment interest in the capital market. The study used a quantitative approach with a survey method of 250 respondents aged 18-30 years in the Jabodetabek area. The instrument was a Likert questionnaire measuring three dimensions of financial literacy: knowledge, attitude, and behavior. Data were analyzed using multiple linear regression. The expected results include identification of the most influential dimensions of literacy, as well as financial education recommendations. This research contributes to OJK policy and digital technology-based education as a form of protection for young investors.